Implementation of Good Governance in the Sidoarjo Regency Regional Library - Sasando Brahmantya; Budi Rianto; Nuhman Nuhman (Syntax Corporation Indonesia, 2023)
This study examines the application of Good Governance in the Sidoarjo Regency Regional Library. This research will be conducted at the Sidoarjo Regional Library by referring and based on that the Sidoarjo Regional Library has made various changes, innovations and strategies in improving service quality, organizational governance, on the other hand the Sidoarjo regional library continues to strive to maintain accreditation status A. The principles used in measuring the implementation of good governance are rule of law, accountability, transparency and openness, professional (professionalism) and participation (participant). So in the end it can be concluded, how the implementation of good governance in the Sidoarjo district's daearah library has been implemented.